(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Mobile Cloud Computing (MCC) is an emerging paradigm that integrates mobile computing and cloud computing to deliver advanced computational capabilities and storage services to mobile devices. MCC addresses the limitations of mobile devices such as restricted processing power, limited battery life, and insufficient storage by offloading intensive tasks to cloud-based resources. This paper provides an in-depth analysis of the MCC architecture, key enabling technologies, significant applications, and prevailing challenges. It concludes by identifying future research directions and emphasizing the importance of edge computing, security frameworks, and energy-efficient algorithms in enhancing the performance and sustainability of MCC systems.